KARAKTERISTIK BALITA KURANG ENERGI PROTEIN (KEP) DI PUSKESMAS SAIGON KECAMATAN PONTIANAK TIMUR TAHUN 2010-2011 - ., Syarifah Sari Safuar (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2014)
Background. Protein Energy Malnutrition (PEM) is the most important nutritionalproblems in developing countries such as Indonesia and a major caused of morbidityand mortality in children under five years old in the world.Objective. The objective of this study is to know the characteristics of the PEMchildren based on World Health Organization (WHO) and National Center for HealthStatistics (NCHS) growth standard. Method. Descriptive study with cross-sectional approach, analyzed medical recordson the year 2010 to 2011 at Saigon Local Health Center of East PontianakSubdistrict.Results. There were 103 children that fulfilled the inclusion criteria. Subject werefound most common in range 12-23 months of age, the ratio between female andmale is 1,6:1. In this study, children with severe underweight, severe stunting andsevere wasting were more common based on WHO growth standard than NCHSgrwoth standard. There were 25 children with marasmus and 3 children withmarasmic kwashiorkor. The most common cormobidities were acute respiratoryinfections (52,42%) followed with diarrhea (17.48%) and tuberculosis (4.84%).Conclusions. There were correlation between nutritional status and comorbidities,which 89,32% PEM children had comorbidities. Keywords: Protein energy malnutrition, children, marasmus, kwashiorkor, growthstandard Â Medical School, Faculty of Medicine, Universitas Tanjungpura Pontianak, WestKalimantan *Department of Pediatric, Faculty of Medicine, Universitas Tanjungpura Pontianak,West Kalimantan **Department of Parasitology, Faculty of Medicine, Universitas TanjungpuraPontianak, West Kalimantan